(untitled) (Journal of Atomic and Molecular Sciences, 2022)
Several fluorescent protein fluorophores with regular substitution were investigated in gas phase using TDDFT with long range corrected functional. Absorption and emission of both neutral and anionic chromophore states were calculated. The spectral shift amplitudes of calculation are in good agreement with experiment. The further intramolecular charge transfer process analysis show that conjugated area, charge transfer number/distance and transfer efficiency can affect spectral shift. Specially, the "N" atom with lone pair electrons of conjugated ring has an important influence on charge transfer process, and the conjugated length between hydroxyl and bridge bond only impact the anionic spectral shift. Our results about fluorescent chromophore spectral red shift mechanism do provide positive clues on new experimental far-red fluorescent protein designing.